2020
DOI: 10.1142/s0217979220401475
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive recycling of 3D printing PLA filament as renewable resources on mechanical and thermal loads

Abstract: 3D printing technology has emerged as a high value-added industry with high efficiency that has dramatically broken away from the existing material and manufacturing industry’s human-based production system. These technologies, ranging from small parts to large structures, are rapidly developing due to the challenge of various filament materials, whereas there are significant concerns about waste filler materials, and complimentary research is needed to improve them. Polylactic acid (PLA), the representative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…The mechanical test revealed that, with R-PLA filament, there was a decrease in tensile strength and hardness by 10.9% and 2.4%, respectively, whereas shear strength improved by 6.8%. In a similar study, Hong et al [ 34 ] reported that with 3D printed R-PLA specimens, tensile and flexural strength reduced by 69% and 53%, respectively, when compared to V-PLA parts. Multiple recycling of PLA causes a decrement in short beam strength.…”
Section: Reuse Of Waste Plastic In Fdmmentioning
confidence: 88%
See 2 more Smart Citations
“…The mechanical test revealed that, with R-PLA filament, there was a decrease in tensile strength and hardness by 10.9% and 2.4%, respectively, whereas shear strength improved by 6.8%. In a similar study, Hong et al [ 34 ] reported that with 3D printed R-PLA specimens, tensile and flexural strength reduced by 69% and 53%, respectively, when compared to V-PLA parts. Multiple recycling of PLA causes a decrement in short beam strength.…”
Section: Reuse Of Waste Plastic In Fdmmentioning
confidence: 88%
“…4 Schematic diagram of the FDM process [ 25 ]
Fig. 5 Recommended FDM nozzle temperature for common thermoplastic materials [ 21 , 29 , 31 34 ]
…”
Section: Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the print job is finished, support material can be mechanically removed or dissolved with appropriate solvent, but in most cases it is mechanically removed. As such, support material if not used in any other function after removal is waste material, but due to the nature of thermoplastics primarily used in AM, it can be recycled and reused in production of new products [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a need to investigate the effect of reprocessing on the mechanical properties of PLA, so the content of recycled material in the composition with neat PLA can be controlled in order to obtain acceptable properties and a quality product (Babagowda et al 2018). Hong et al (2020) investigated the effect of mechanical recycling on PLA filament for 3D printing, aiming to evaluate mechanical and thermal properties. The glass transition temperature (Tg), the cold crystallization temperature and the degree of crystallinity of the reprocessed PLA is less than what is found in virgin PLA, contributing to a decrease in tensile Research, Society and Development, v. 9, n. 12, e13291210767, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.10767 5 and flexural strengths.…”
Section: Introductionmentioning
confidence: 99%